Interferometry of infragravity waves off New Zealand. Issue 2 (18th February 2014) - Godin, Oleg A.; Zabotin, Nikolay A.; Sheehan, Anne F.; Collins, John A.
Abstract Wave interferometry is a remote sensing technique, which is increasingly employed in helioseismology, seismology, and acoustics to retrieve parameters of the propagation medium from two‐point cross‐correlation functions of random wavefields. Here we apply interferometry to yearlong records of seafloor pressure at 28 locations off New Zealand's South Island to investigate propagation and directivity properties of infragravity waves away from shore. A compressed cross‐correlation function technique is proposed to make the interferometry of dispersive waves more robust, decrease the necessary noise averaging time, and simplify retrieval of quantitative information from noise cross correlations. The emergence of deterministic wave arrivals from cross correlations of random wavefields is observed up to the maximum range of 692 km between the pressure sensors in the array. Free, linear waves with a strongly anisotropic distribution of power flux density are found to be dominant in the infragravity wavefield. Lowest‐frequency components of the infragravity wavefield are largely isotropic. The anisotropy has its maximum in the middle of the spectral band and decreases at the high‐frequency end of the spectrum. Highest anisotropy peaks correspond to waves coming from portions of the New Zealand's shoreline. Significant contributions are also observed from waves propagating along the coastline and probably coming from powerful sources in the northeast Pacific. Infragravity wave directivity is markedly different to the east and to the west of the South Island. The northwest coast of the South Island is found to be a net source of the infragravity wave energy.